Rapid synthesis of high-areal-capacitance ultrathin hexagon Fe2O3 nanoplates on carbon cloth via a versatile molten salt method. (27th July 2020) - Gu, Yi-Jie; Wen, Wei; Zheng, Shilie; Wu, Jin-Ming
Abstract : A molten salt method is developed to coat ultrathin hexagon Fe2 O3 nanoplates on carbon cloth within 1 min, which simultaneously activates the carbon fibers, for flexible supercapacitors with a high areal capacitance. Abstract : Earth abundant and environmentally benign iron oxides are ideal candidates for electrochemical energy storage. We report herein a rapid (within 1 min), facile one-step molten salt method to homogeneously coat various metal oxides of Fe2 O3, Mn3 O4, Co3 O4, NiO, CuO, ZnO, etc. on carbon cloth (CC) for supercapacitor applications. In particular, ultra-thin Fe2 O3 nanoplates coated on CC (Fe2 O3 @CC) connected in series to form a porous structure. Nanoplates have a larger specific surface area and hence more active sites for electrochemical reactions and the porous architecture effectively relieves the volume expansion of Fe2 O3 during charging/discharging, which avoids the structural collapse and benefits the cycling stability. As a result, the Fe2 O3 @CC exhibits a large areal capacitance of 4175.7 mF cm −2 at a scan rate of 2 mV s −1 in −1.0–0 V vs. Hg/HgO, thanks also to the carbon cloth substrate activated simultaneously by the molten salt. The Fe2 O3 @CC electrode is especially appropriate for high current density (over 10 mA cm −2 ) charging/discharging. A Mn3 O4 @CC positive electrode is also synthesised via the molten salt method, and then coupled with the Fe2 O3 @CC negative electrode to assemble a 2 V high-voltage asymmetric supercapacitor (ASC) in 6 M KOH aqueous electrolyte. The Mn3 O4 @CC//Fe2 O3 @CC ASC delivers a high energy density of 2.91 mW h cm −3 at a power density of 25 mW cm −3 and a high power density of 278 mW cm −3 with a corresponding energy density of 1.25 mW h cm −3 . An excellent cycling performance of 96% capacitance retention after 10 000 cycles at a high current density of 10 mA cm −2 is also recorded. The facile, versatile synthetic method and resultant high-performance electrodes are promising for practical applications in flexible electrochemical energy storage.